Dividend Policy and Earnings Management: An Exploratory Study Between Pre and Post Changing a Company Name That Listed in Bursa Malaysia - Norfhadzilahwati, Rahim (2010)
This paper is able to determine whether changing a company name will give effect to the dividend policy. This study investigated the implication pre and post companies changed their company name. Then, the study will focus particularly on the increment and decrement on earnings management will give impact on dividend policy between changing a company name and non-changing a company name. The study uses the period of year 2003 until year 2009.as the forecast sample period in determining dividend policy and earnings management. Dividend Payout Ratio is the amount of dividend paid relative to the company's earning. Dividend Yield is defined as the rate of current income earned on the investment dollar. Besides that, the earnings management includes Net Income, Earnings per Share, Retained Earnings, Net Profit Margin, Return on Asset and Return on Common Equity. In using the information from the data collection, we can evaluate the effect of Net Income, Earnings per Share, Retained Earnings, Net Profit Margin, Return on Asset and Return on Common Equity to the Dividend Payout Ratio and Dividend Yield. Furthermore, this paper also analyzed the effect between dividend policy and earnings management on the company performance. The result indicated that Return on Asset and Return on Common Equity are positively correlated with dividend payout and yield.